Tatwir Wasilah Samiyah Basoriyah Fi Tadris Al-Mufradat Bistikhdam Benime Li As-Shaf As-Sabi Fi Al-Madrasah Al-Tsanawiyah Al-Hukumiyah 1 Payakumbuh - Yatasya Syukri; Rehani Rehani; Fauzana Annova (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
AbstractVocabulary is a important element in learning Arabic. Without learning it is impossible to master language skills, namely listening, speaking, reading and writing. But student’s understanding of vocabulary is still lacking, one of the contributing factors is the teachers still use conventional media. This article focus on developing vocabulary learning media using Benime. The purpose of this study was  described of need analysis, design, develop and disseminate of vocabulary learning media using Benime. The method used is Research and Development with model 4D. The results showed that needs analysis of teacher with the value of 100 %  and students of 90,16 %. Assessment of media validator 88,88 % and matter validator 82,14 %. Practicality of the media based on teacher responses shows the value 91,50%  and students responseof 86,76 %. The effectiveness of the media seen from the pretest results 70,14 and posttest results 92,50.